2014
DOI: 10.1007/s10886-014-0493-2
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Preen Oil Composition Pertaining to Season, Sex, and Genotype in the Polymorphic White-Throated Sparrow

Abstract: Evidence for the the ability of birds to detect olfactory signals is now well documented, yet it remains unclear whether birds secrete chemicals that can be used as social cues. A potential source of chemical cues in birds is the secretion from the uropygial gland, or preen gland, which is thought to waterproof, maintain, and protect feathers from ectoparasites. However, it is possible that preen oil also may be used for individual recognition, mate choice, and signalling social/sexual status. If preen oil sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…To test for differences between black-capped and Carolina chickadees in uropygial oil chemical profiles, we first conducted a principal components analysis (PCA) on the transformed gas chromatograph data (N = 81) to reduce the dataset of 146 different compounds into a smaller number of principal components (PCs). PCA is the most common method used to analyze avian preen oil chemistry (Amo et al, 2012;Fischer, Haliński, Meissner, Stepnowski, & Knitter, 2017;Leclaire et al, 2012;Lopez-Perea & Mateo, 2019;Shaw, Rutter, Austin, Garvin, & Whelan, 2011;Tuttle et al, 2014;Whittaker et al, 2013;Whittaker et al, 2019;Whittaker et al, 2018;Whittaker et al, 2010;Zhang et al, 2013) and it allows an examination of which factors best explain the main axes of variation in our data, represented by PCs. We used a multivariate analysis of variance (MANOVA) on nontrivial principal components selected based on comparing a scree plot of the principal components with a broken-stick distribution (Jackson, 1993), using species, date, sex, and all interactions as fixed factors.…”
Section: Uropygial Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test for differences between black-capped and Carolina chickadees in uropygial oil chemical profiles, we first conducted a principal components analysis (PCA) on the transformed gas chromatograph data (N = 81) to reduce the dataset of 146 different compounds into a smaller number of principal components (PCs). PCA is the most common method used to analyze avian preen oil chemistry (Amo et al, 2012;Fischer, Haliński, Meissner, Stepnowski, & Knitter, 2017;Leclaire et al, 2012;Lopez-Perea & Mateo, 2019;Shaw, Rutter, Austin, Garvin, & Whelan, 2011;Tuttle et al, 2014;Whittaker et al, 2013;Whittaker et al, 2019;Whittaker et al, 2018;Whittaker et al, 2010;Zhang et al, 2013) and it allows an examination of which factors best explain the main axes of variation in our data, represented by PCs. We used a multivariate analysis of variance (MANOVA) on nontrivial principal components selected based on comparing a scree plot of the principal components with a broken-stick distribution (Jackson, 1993), using species, date, sex, and all interactions as fixed factors.…”
Section: Uropygial Oilsmentioning
confidence: 99%
“…PCA is the most common method used to analyze avian preen oil chemistry(Amo et al, 2012;Fischer, Haliński, Meissner, Stepnowski, & Knitter, 2017;Leclaire et al, 2012;Lopez-Perea & Mateo, 2019;Shaw, Rutter, Austin, Garvin, & Whelan, 2011;Tuttle et al, 2014;Whittaker et al, 2013;Whittaker et al, 2019; PCA is the most common method used to analyze avian preen oil chemistry(Amo et al, 2012;Fischer, Haliński, Meissner, Stepnowski, & Knitter, 2017;Leclaire et al, 2012;Lopez-Perea & Mateo, 2019;Shaw, Rutter, Austin, Garvin, & Whelan, 2011;Tuttle et al, 2014;Whittaker et al, 2013;Whittaker et al, 2019; …”
mentioning
confidence: 99%
“…[4] Secretion of this gland play an important role in a feather maintenance, waterproofing feather, and may be associated with intraspecific communication and defense against the microbial, parasitic agent and predators . [5,6,7,8,9] However, in few birds like…”
Section: Introductionmentioning
confidence: 99%
“…Different compounds, including octenol, ammonia and lactic acid, have been reported as attractants to mammophilic mosquitoes such as Anopheles gambiae (Takken & Knols, ). Birds produce, in their uropygial gland, a mixture of organic compounds that varies between species, ages and sexes (Tuttle et al ., ; Moreno‐Rueda, ), which they spread over their plumage when preening and which mainly functions as waterproofing and conditioning for plumage. This secretion has been reported to attract insect vectors such as mosquitoes (Russell & Hunter, ), whereas other studies have found the opposite (i.e.…”
mentioning
confidence: 99%